Association of Migraine Headaches With Suicidal Ideation Among Pregnant Women in Lima, Peru. - Friedman, Lauren E (2016)
BACKGROUND: Suicide is a leading cause of maternal death globally, and suicide prevalence rates have been shown to be increased in those with migraine. No previous study has examined the association between migraine and suicidal ideation during pregnancy. OBJECTIVE: To examine the association between migraine and suicidal ideation among a cohort of pregnant women. METHODS: A cross-sectional study was conducted among 3372 pregnant women attending prenatal care clinics in Lima, Peru. Suicidal ideation and depression were assessed using the Patient Health Questionnaire-9 (PHQ-9) scale during early pregnancy. Migraine classification (including migraine and probable migraine) was based on International Classification of Headache Disorders-III beta criteria. Multivariable logistic regression analyses were performed to estimate odds ratios (OR) and 95% confidence intervals (95%CI). RESULTS: Suicidal ideation was more common among those with migraine (25.6%) as compared to those with probable migraine (22.1%, P < .001) or non-migraineurs (12.3%, P < .001). After adjusting for confounders, including depression, those with migraine or probable migraine had a 78% increased odds of suicidal ideation (OR = 1.78; 95% CI: 1.46-2.17), as compared with non-migraineurs. Women with both migraine and depression had a 4.14-fold increased odds of suicidal ideation (OR = 4.14; 95% CI: 3.17-5.42) compared to those with neither condition. CONCLUSION: Migraine is associated with increased odds of suicidal ideation in pregnant women even when controlling for depression. These findings support the consideration of screening women with comorbid migraine and depression for suicidal behavior during pregnancy.